Conducting behavioral and social-emotional assessments in MTSS : screen to intervene - Von der Embse, Nathaniel Paul; Eklund, Katie; Kilgus, Stephen P. (New York, NY : Routledge, 2022)
Conducting Behavioral and Social-Emotional Assessments in MTSS: Screen to Intervene offers effective assessment strategies for improving mental and behavioral health decision-making within multi-tiered systems of support. Accessible to school psychologists, behavior analysts, PBIS team leaders, and other school-based professionals, this applied book features evidence-based practices and case study examples to show how assessment data can drive prevention and intervention services, particularly at Tiers1 and 2. Specific tools and recommendations for universal screening, problem analysis, and progress monitoring procedures offer a fresh, real-world approach to data-driven implementation of supports across schools.
Keywords: Educational counseling; Students -- Mental health services; Behavioral assessment of children; Behavioral assessment of teenagers; EDUCATION / Educational Psychology; EDUCATION / Counseling / General